Does metal porosity affect metal ion release in blood and urine following total hip arthroplasty? A short term study. Issue 5 (September 2018) - Bistolfi, Alessandro; Cimino, Andrea; Lee, Gwo-Chin; Ferracini, Riccardo; Maina, Giovanni; Berchialla, Paola; Massazza, Giuseppe; Massè, Alessandro
Introduction: The surface area of exposed metal in a trabecular-titanium acetabular component is wider compared to traditional-titanium implants. The purpose of this study is to establish if this increase in surface area can lead to a significant increase in systemic metal levels. Methods: 19 patients with conventional acetabular component and 19 with trabecular-titanium cup were compared. Aluminum, Vanadium and Titanium in blood and urine were assessed before surgery and at intervals for 2 years. The samples were analysed using an inductively coupled plasma mass spectrometry. Results: Patients with trabecular-titanium did not have significantly higher metal ion levels compared to patients with conventional cups up to 2 years. A trend over time was statistically significant in both blood and urine for aluminum and titanium concentrations. Conclusions: The three-dimensionality and the wide surface of the trabecular-titanium acetabular component did not affect metal ion release compared to traditional implants after 2 years.